APPLICATION METHODS LIQUID SCINTILLATION COUNTING (LSC) IN DETERMINING CONCENTRATION OF BIO SOLAR - Rahmawati Rahmawati; Alfian Noor; Maming Gaffar; Muhammad Zakir (Marina Chimica Acta, 2016)
Research on the use of a liquid scintillation counter method in determining the concentration of biodiesel in the market has been carried out by taking samples of biodiesel in Pertamina. Preparation done by creating a standard biodiesel and biodiesel mixed with diesel at a certain concentration. Biodiesel is chemically formed by the transesterification and esterification process is converted into methyl ester triglycerides with the help of H2SO4 and NaOH as a catalyst. Total carbon in the sample solution is 1.5690 g/8 mL obtained through methods spekktrofotometri uv-vis. The method of determining the concentration of a specific activity based on measurements of samples obtained from the shredded Liquid Scintilation Counter (LSC) Hidex 300 SL, ie 11.5902 DPM / gC. By using the specific activity of the sample and the specific activity was added to standard linear equations of the obtained sample concentration of biodiesel amounted to 18.81%.